Kontribusi Wanita Tani Penyadap Karet Terhadap Peningkatan Pendapatan Keluarga - Prayoga, Eko Riyan (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2016)
ABSTRACTThe role of women farmers in rural areas is very important, in addition to taking care of the household and the children of women farmers also work to earn additional income for their families, various types of work can be done by a woman both self-employed and farming. In this study jobs occupied by women farmers are tapping rubber (cut). Techniques of data collection using surveys and interviews. Data analysis technique used is quantitative analysis. Results of a study of the role of women farmers to the family income in the Pasir Utama Village In Sub District Rambah Rokan Hulu Regency contributed revenue of Rp.210.977.559/ year and accounted for 31,98% of total revenues family. The revenueis no separation with her husband acceptance. In addition to acceptance of thepeasant womans husbands income is used to meet household needs. These needsinclude basic daily needs, the needs of school children and other social needssuch as gathering and help people who have a celebration.Keywords: Role of Women, Income, Contributions